Conflict Mapping in the Rempang Eco City National Strategic Project on Rempang Island Batam City - Putra, Edi; Darmawan, Eki (Journal of Indonesian Rural and Regional Government, 2025)
The planned development of the Rempang Eco City (REC) National Strategic Project (PSN) in Rempang, Batam, continues to face resistance from many members of the Rempang indigenous community. This resistance has sparked conflict between the community and the Batam Free Trade Zone Authority (BP Batam), the Batam City Government, and PT MEG as the developer. Issues regarding customary land and agrarian affairs often trigger conflicts in regional development. This study aims to examine and map the sources of conflict and the parties responsible for the Rempang conflict. The theory used in this study is a decentralization and conflict approach. This study employed a qualitative method with a descriptive qualitative research design, which objectively and in detail describes the conflict that occurred on Rempang Island. Data collection techniques included a literature review of legislation, scientific journals, articles, news reports, press releases, and other documents relevant to the research topic, supported by field interviews. The results of this study conclude that there are three main factors that constitute the source of conflict: first, historical factors, culture, customs, and customary land. Second, factors of coercion and repressive actions by law enforcement officers, as well as criminalization, thuggery, and intimidation by BP Batam and the company. This factor also contributes to the escalating conflict over the PSN REC. Third, the Batam Free Trade Zone Authority's (BP Batam) non-humanistic and non-harmonious approach to the Rempang community. Several parties consider the source of this conflict to be the responsibility of BP Batam, the Regional Governments: Batam City Government, Riau Islands Provincial Government, Batam City Council (DPRD) and Riau Islands Provincial Council (DPRD), the Central Government: the President, the Ministry of Investment and the Ministry of Economy, and the company: PT MEG.